English Storytelling Competition untuk Penguatan Kompetensi Bahasa Inggris dan Pelestarian Budaya Lokal Generasi Muda Mimika - Azwar Fadlan; Deasy Natalia Lessu (Lembaga Pengembangan Kinerja Dosen, 2025)
Low English proficiency remains a problem for the younger generation in Mimika Regency, particularly in speaking skills. Additionally, the flow of modernization influences the low appreciation of society, especially the younger generation, towards local culture, with the emergence of popular culture. This community service activity offers an English Storytelling Competition as a creative and innovative educational medium to integrate English competency and the preservation of the local culture of indigenous communities in Mimika Regency. This program used a collaborative approach/community-based participatory approach (CBPA) through community involvement in the planning, script preparation, workshops, competitions, and reflection stages, together with the utilization of existing local strengths and wisdom. The main purpose of this program is to encourage social change in the community, which includes: (1) increasing oral English skills in the young generation in Mimika. (2) the presence of awareness and pride in the importance of preserving local culture, and (3) the creation of a community environment that provides appreciation for local cultural products that grow together with global challenges. The results of the activity showed an increase in English communication skills, growing self-confidence in students, and the presence of creativity in interestingly packaging Amungme-Kamoro folklore. In addition, this activity brings a new awareness of the importance of preserving local culture, potential leaders who dare to appear in public, and presents a new institution in the form of a space competition that combines aspects of language and cultural education.